ANALISIS YURIDIS ATAS PUTUSAN PTUN TERKAIT DENGAN PROSES PEMBATALAN KEPUTUSAN TATA USAHA NEGARA - Rian Delvino Pramudya; Yudi Kornelis; Diki Zukriadi (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This research aims to analyze normative juridically the decisions of the State Administrative Court (PTUN) related to the process of canceling State Administrative decisions (TUN). The method used in this research is a normative juridical method with a statutory approach and relevant cases. Analysis was carried out on PTUN decisions related to the process of canceling TUN decisions, both from a substantive and procedural perspective. The research results show that the PTUN tends to make decisions based on the principles of state administrative law, such as fairness, feasibility, and compliance with established procedures. However, there are challenges in implementing PTUN decisions that require further attention from relevant parties to ensure effectiveness and fairness in enforcing state administrative law. It is hoped that this research can contribute to deepening understanding of the process of canceling TUN decisions through a normative juridical perspective. Keywords: State administrative justice; Cancellation of State Administrative Decisions; Juridical Analysis